Epidemiology of Epstein-Barr virus-associated pediatric lymphomas from Argentina - Paola Chabay; María Victoria Preciado (Permanyer, 2016)
More than 90% of the population is infected by Epstein-Barr virus (EBV), which has sophisticatedly evolved to survive silently in B cells for the life of infected individuals. However, if the virus-host balance is disturbed, latent EBV infection could be associated with several lymphomas. The age at primary infection varies substantially worldwide, and exposure to EBV is likely to be due to socioeconomic factors. In Argentina, EBV infection is mostly subclinical and 90% of patients are seropositive by the age of 3 years; therefore, its epidemiological characteristics resemble those of an underdeveloped or developing population. EBV-positive Hodgkin lymphoma (HL) in young adults from developed populations has been attributed to delayed primary EBV infection as suggested by the association with recent mononucleosis development. EBV-associated Burkitt lymphoma and Hodgkin lymphoma in children from Argentina display frequencies similar to those observed in developed countries, whereas EBV presence in pediatric diffuse large B-cell lymphoma is slightly increased compared to those populations. However, EBV presence is statistically associated particularly with patients < 10 years of age in all three entities. Therefore, a relationship between low age of EBV seroconversion and B-cell lymphoma development risk could be suggested in children from Argentina.